Instructing and Mentoring Ex-Con University Students in Departments of Criminology and Criminal Justice. Issue 2 (3rd April 2019) - Tewksbury, Richard; Ross, Jeffrey Ian
ABSTRACT: Recognizing the growing presence of university students who are also ex-cons, this article discusses the challenges of working with such individuals and offers practical suggestions for ways to enhance such interactions. The effects of institutional socialization, cultural differences, and a range of abilities and motivations presented by ex-con students requires a need to design and implement unique instructional, especially mentoring, approaches that are most likely to be successful.